A systematic review and meta-analysis of cold exposure and cardiovascular disease outcomes - Fan, Jie-Fu; Xiao, Yu-Chen; Feng, Yi-Fei; Niu, Lu-Yu; Tan, Xing; Sun, Jia-Cen; Leng, Yue-Qi; Li, Wan-Yang; Wang, Wei-Zhong; Wang, Yang-Kai (Frontiers in Cardiovascular Medicine, 2023)
Background Cold exposure has been considered an essential risk factor for the global disease burden, while its role in cardiovascular diseases is still underappreciated. The increase in frequency and duration of extreme cold weather events like cold spells makes it an urgent task to evaluate the effects of ambient cold on different types of cardiovascular disease and to understand the factors contributing to the population's vulnerability. Methods In the present systematic review and meta-analysis, we searched PubMed, Scopus, and Cochrane. We included original research that explored the association between cold exposure (low temperature and cold spell) and cardiovascular disease outcomes (mortality and morbidity). We did a random-effects meta-analysis to pool the relative risk (RR) of the association between a 1°C decrease in temperature or cold spells and cardiovascular disease outcomes. Results In total, we included 159 studies in the meta-analysis. As a result, every 1°C decrease in temperature increased cardiovascular disease-related mortality by 1.6% (RR 1.016; [95% CI 1.015–1.018]) and morbidity by 1.2% (RR 1.012; [95% CI 1.010–1.014]). The most pronounced effects of low temperatures were observed in the mortality of coronary heart disease (RR 1.015; [95% CI 1.011–1.019]) and the morbidity of aortic aneurysm and dissection (RR 1.026; [95% CI 1.021–1.031]), while the effects were not significant in hypertensive disease outcomes. Notably, we identified climate zone, country income level and age as crucial influential factors in the impact of ambient cold exposure on cardiovascular disease. Moreover, the impact of cold spells on cardiovascular disease outcomes is significant, which increased mortality by 32.4% (RR 1.324; [95% CI 1.2341.421]) and morbidity by 13.8% (RR 1.138; [95% CI 1.015–1.276]). Conclusion Cold exposure could be a critical risk factor for cardiovascular diseases, and the cold effect varies between disease types and climate zones. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO, identifier: CRD42022347247.